China's first pulsed neutron source - Chen, Hesheng; Wang, Xun-Li (Nature materials, 2016)
The China Spallation Neutron Source is expected to produce its first beam in 2017. Hesheng Chen and Xun-Li Wang provide an overview of this user facility and what it means for science in China and elsewhere.